Teacher in social role of manager and of leader - Valisowa, Alena (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The study addresses the specifics of the educational management at the universities in the Czech Republic. It defines its differences and also common features in relation to the leadership and stresses their interconnection in the processes of systematic planning, organizing, financing, monitoring, leadership of people, controlling and evaluation. The educational management is also a field of study at some universities with technical, economical and humanistic specialization.